2018
DOI: 10.1021/acsnano.7b08682
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Plasmon-Enhanced Second-Harmonic Generation from Monolayer Tungsten Diselenide on Flexible Substrates

Abstract: Monolayer two-dimensional transition-metal dichalcogenides (2D TMDCs) exhibit promising characteristics in miniaturized nonlinear optical frequency converters, due to their inversion asymmetry and large second-order nonlinear susceptibility. However, these materials usually have very short light interaction lengths with the pump laser because they are atomically thin, such that second-harmonic generation (SHG) is generally inefficient. In this paper, we fabricate a judiciously structured 150 nm-thick planar su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 51 publications
(93 reference statements)
3
92
0
Order By: Relevance
“…Regarding the plasmon resonance, the electric field enhancement factor could be further enhanced by patterning the metal film to form a nanostructure. Wang et al reported a 7000‐fold SHG enhancement of monolayer WSe 2 on an Au film with sub‐20 nm trench (Figure E) . The presence of trenches could provide much stronger near field enhancement compared with planar Au film.…”
Section: Modulation and Enhancement Of Nlomentioning
confidence: 94%
See 4 more Smart Citations
“…Regarding the plasmon resonance, the electric field enhancement factor could be further enhanced by patterning the metal film to form a nanostructure. Wang et al reported a 7000‐fold SHG enhancement of monolayer WSe 2 on an Au film with sub‐20 nm trench (Figure E) . The presence of trenches could provide much stronger near field enhancement compared with planar Au film.…”
Section: Modulation and Enhancement Of Nlomentioning
confidence: 94%
“…Copyright 2015, The Royal Society of Chemistry. E, Au trench‐enhanced SHG of monolayer WSe 2 . Copyright 2018, American Chemical Society.…”
Section: Modulation and Enhancement Of Nlomentioning
confidence: 99%
See 3 more Smart Citations